Reversible data hiding in encrypted images with RSA and El gamal algorithm - R. Bhat, Chethan; Kishore, B. (International Journal of Engineering and Technology, 2018)
This paper puts forward reversible concealing plans for figure content pictures encoded by techniques for open key cryptosystems with probabilistic and homomorphic properties. Inside the reversible plan despite the fact that a direct contortion is presented, the inserted infor-mation might be separated, and the special picture might be recuperated from the immediately unscrambled photograph. With the combined strategy, a beneficiary may evacuate a bit of inserted data before unscrambling and expel some other piece of installed data and recuperate the genuine plaintext picture post-decoding. Here we propose to actualize the RSA and ElGamal consolidated calculation for picture encod-ing and decoding.Â Â Â